2020
DOI: 10.1177/0972150920961254
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Wallets: Theoretical and Empirical Analysis

Abstract: Mobile wallets (m-wallet) have played a prominent role in changing our system of payment from cash to digital payment. The current study employs a systematic review of articles published on m-wallets between January 2008 and January 2020. To identify the relevant studies, research databases are searched using different keywords. Research articles published on m-wallets are selected based on particular inclusion criteria and clustered on the basis of keywords, abstract and title. To ensure a reasonable accuracy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“…In India, the Digital India initiative in 2015, the demonetization of bank currency notes in 2016 and the outbreak of the Covid-19 Pandemic in 2019 stimulated the adoption of M-wallets mobile applications (Raman and Aashish, 2021;Kapoor et al, 2020). Initially, M-wallet usage was perceived as a status symbol at the introduction stage because the consumer's early adoption of technology innovation is associated with status and conspicuous consumption (Arbore et al, 2014).…”
Section: Developing Prestigious Mass Brands 533mentioning
confidence: 99%
See 1 more Smart Citation
“…In India, the Digital India initiative in 2015, the demonetization of bank currency notes in 2016 and the outbreak of the Covid-19 Pandemic in 2019 stimulated the adoption of M-wallets mobile applications (Raman and Aashish, 2021;Kapoor et al, 2020). Initially, M-wallet usage was perceived as a status symbol at the introduction stage because the consumer's early adoption of technology innovation is associated with status and conspicuous consumption (Arbore et al, 2014).…”
Section: Developing Prestigious Mass Brands 533mentioning
confidence: 99%
“…In India, the Digital India initiative in 2015, the demonetization of bank currency notes in 2016 and the outbreak of the Covid-19 Pandemic in 2019 stimulated the adoption of M-wallets mobile applications (Raman and Aashish, 2021; Kapoor et al. , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…We notice the extensive application of TAM and its extension, UTAUT (Venkatesh et al 2003 ) in understanding the motives and nature of the behaviour of the consumers for using M-Wallets and electronic payments. The studies in various countries, including India (Aydin and Burnaz 2016 ; Pousttchi and Wiedemann 2007 ; Chen and Nath 2008 ; Shin 2009 ; Yang et al 2012 ; Liébana-Cabanillas et al 2014 , 2020b ; Dwivedi et al 2014 ; Kapoor et al 2014 , 2020 ; Phonthanukitithaworn et al 2015 ; Yadav 2016 ; Manikandan and Jayakodi 2017 ; Mei and Aun 2019 , Pal et al 2020 ; Singh and Sinha 2020 ; Singh et al 2020 ), revealed various factors influencing the decisions to use M-Wallets. Mobile technology solutions such as consumer attitude, expectancy about performance, innovative applications, facilitation, convenience, user-friendliness, speed of transaction, compatibility issues, social pressure, information security and privacy, trust, cost of operations, and rewards influence the consumers.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is quite imperative to consider their views also. In another recent study (Kapoor et al 2020 ), the authors argued for developing appropriate service quality dimensions for comparing solution providers. They applied a fuzzy-TOPSIS framework.…”
Section: Introductionmentioning
confidence: 99%
“…Mobile wallet (m-wallet) is among one such mobile commerce initiatives which emerged as one of the innovative touch free payment solutions. M-wallet facilitates users by allowing them to utilise payments and loyalty cards, make peer-to-peer payments, save e-receipts, pay bills, and use coupons directly from application, thereby enabling users’ money to move along with their smartphones ( Kapoor et al, 2020 , Mew and Millan, 2021 ). M-wallets can also be utilised to store sensitive information such as passports, insurance policies and online shopping accounts in an encrypted format ( Shin, 2009 , Shankar, 2021 ).…”
Section: Introductionmentioning
confidence: 99%